Analysis of the Role of Sebum Levels in the Incidence of Acne Vulgaris in Adolescents: An Observational Study on Adolescents in Jakarta, Indonesia - Arni Ismi Fadhila; Tansil Tan, Sukmawati (Community Medicine and Education Journal, 2024)
Acne vulgaris (AV) is a chronic inflammatory skin condition common in adolescents, with excess sebum production considered a major risk factor. This study aims to analyze the relationship between sebum levels and the incidence of AV in adolescents in Jakarta, Indonesia. Cross-sectional observational research was conducted on 300 adolescents aged 12-18 years in Jakarta. Sebum levels were measured using Sebumeter, and AV incidence was assessed based on Global Acne Grading System (GAGS) criteria. Statistical analysis was carried out using the chi-square test, independent t-test, and logistic regression. There is a significant relationship between high sebum levels and the incidence of AV (p < 0.001). Adolescents with high sebum levels have a 3.9 times higher risk of experiencing AV compared to adolescents with normal sebum levels (OR = 3.9; 95% CI = 2.4-6.3). Other factors such as age, gender, socioeconomic status, body mass index (BMI), face washing habits, use of cosmetics, and family history of AV do not have a significant effect on the incidence of AV. Sebum level is an independent risk factor for the incidence of AV in adolescents in Jakarta. Early detection and effective management of sebum levels can be an important strategy in the prevention and treatment of AV.